Effects of alkoxide alteration on the ring-opening polymerization of ε-caprolactone initiated by n-Bu3SnOR: a DFT study - Sattayanon C. (Springer New York LLC, 2014)
The ring-opening polymerization (ROP) of ε-caprolactone (CL) initiated by tributyltin alkoxides (n-Bu3SnOR), where R = methyl (Me), ethyl (Et), propyl (Pr), and butyl (Bu), was investigated using density functional theory at B3LYP level with mixed basis set. A coordination–insertion mechanism with two transition states was found for all ROP reactions: (1) starting with a coordination of CL onto Sn center led to a nucleophilic addition of the carbonyl group of CL, (2) followed by the exchange of alkoxide ligand with Sn atom and the ROP of CL was completed through classical acyl-oxygen bond cleavage. The barrier heights of all reactions with different initiators were calculated using potential energy profiles. All ROP reactions initiated with n-Bu3SnOR demonstrated exothermic reaction and the rate-determining step was the first transition state. The ROP of CL with n-Bu3SnOMe has the smallest value of barrier height compared to other reactions. Moreover, the activation energies for all ROP reactions, calculated using the transition state theory with TheRATE program, are in good agreement with available experimental data.